Proses Identifikasi: Mengenal Anak Kesulitan Belajar Tipe Disleksia Bagi Guru Sekolah Dasar Inklusi - Rofiah, Nurul Hidayati (INKLUSI, 2015)
One of the common and yet not well understood learning difficulties is dyslexia. Most teachers in Indonesia are still not equipped with enough information or knowledge to enable them to identify this learning difficulty. As such, most students with dyslexia are undiagnosed and as a resulttheir learning needs are not properly met. This paper argues that identification and assessment are important steps to developingan appropriate learning plan for a student with dyslexia. The identification process can be done by teachers through careful and systematic observation. Further, steps of identification can be done through in depth interviews with both students and parents as well as other means of assessment such as assignment or standardized psychological testing.This paper also argues that in the case of dyslexia,early intervention will minimize children’s social and emotional challenges. At the elementary school level the psychological challenges can include low self-esteem, feelings of incompetence, and powerlessness which will easily lead a student with dyslexia to be the object of peer bullying. The absence of proper identification and assessment also often leads teachers and parents to misdiagnose dyslexic children as those with mental disabilities.